Connectionist networks for phoneme recognition - Van der Merwe, J. J. N.(Jacobus Johannes Nicolaas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Electronics)) -- University of Stellenbosch, 1990.